PROGRAM PENGENALAN ARTIFICIAL INTELLIGENCE UNTUK UMKM DENGAN CHATGBT UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM - Budiningrum, Endah Wening; Hartadi, Agung; Nugroho, Nurhadi; Purwanta, Purwanta; Fathoni, Muhammad Isnaini (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Artificial intelligence (AI) is part of a new generation of technology that can facilitate the competitive advantage of MSMEs. Because the Indonesian economy is largely driven by MSMEs, the application of AI to MSMEs is a key factor in the success of the national economy. This AI introduction program for MSMEs aims to introduce AI that is beneficial for the sustainability of MSME businesses, where currently it is felt that the struggle for MSMEs to continue to survive is quite difficult. The implementation of the AI ​​community empowerment program for MSMEs is carried out in collaboration with the Koperasi Serba Usaha Ikatan Pengrajin Sleman (KSU IKAPIM), which is a cooperative whose members are MSMEs in Sleman Regency, DIY. This service activity is carried out through several stages, namely the survey stage, socialization and training, mentoring and finally the evaluation stage. AI can increase MSME product sales through accurate customer data analysis, customer personalization, chatbots and automated customer service, targeted marketing with a clear target market, customer sentiment analysis, business process automation such as inventory management, scheduling and order processing, demand prediction, price optimization which helps in setting prices, better ad management, and better product development. By incorporating AI into their operations, MSMEs can increase efficiency, optimize marketing strategies, and improve customer experience, all of which can contribute to increased sales of their products.